Optimalisasi Evaluasi Pembelajaran Melalui Tes Hasil Belajar Dan Program Tindak Lanjut: Perspektif Sejarah Dan Implementasi - Bilal; Aulan; Dhaifah Khairunnisa Bilge; Sani Safitri; Rani Oktapiani (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
Learning evaluationplays an important role in ensuring the optimal achievement of educational goals.This study aims to analyse efforts to optimise learning evaluationthrough learning outcome tests and follow-up programmes, withreference to historical perspectives and their application in the context of education inIndonesia. The research method used is a study and literature review. The results of theresearch show that the evaluation process has undergone significant developments, from conventional systems to more comprehensiveand digital-based approaches that focus on the student learning process. Learning outcome testsplay a crucial role in monitoring student progress through formative, summative, diagnostic, and placement assessments. In addition, follow-up programmes in the form of remedial and enrichment learning are important strategiesfor improving learning outcomes and learning quality.The application of optimisation in Indonesia has been reflected through education policy, theuse of technology in evaluation, and the application of item analysis toensure the validity and reliability of assessments.